PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE NHT (NUMBER HEAD TOGETHER) DENGAN MODEL PEMBELAJARAN MAKE A MATCH PADA MATA PELAJARAN IPA MATERI CAHAYA DAN SIFATNYA DI KELAS V SD NEGERI 094166 SIDOTANI 1 TAHUN AJARAN 2022/2023 - Herna Jusnita Samosir (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
The problem in this research is the learning outcomes of students who have not completed classically in the science subject on light and its characteristics in class V SD Negeri 094166 Sidotani I Academic Year 2022/2023. This is because the implementation of learning is still teacher-centered. This study aims to find out whether the learning outcomes of students using the Number Head Together model are better than using the Make A Match model in the science subject on light and its characteristics. This type of research is quasi-experimental. This research was conducted at SD Negeri 094166 Sidotani L. The population for this study was all fifth grade students at SD Negeri 094166 Sidotani I, totaling 40 students and divided into two parallel classes. Data collection tools used were tests and data analysis used were normality tests, homogeneity tests. , the hypothesis test used was the two difference test. average (test 7). From the results of data analysis, it was obtained that student learning outcomes in the science subject matter of light and its characteristics after using the Number Head Together cooperative learning model in class V SD Negeri 094166 Sidotani I Academic Year 2022 / 2023 an average value of 86.93 was obtained and student learning outcomes using the Make A Match learning model obtained an average value of 167.93. So it can be concluded that student learning outcomes in the natural sciences subject of light and its nature were taught using the Number Head Together cooperative learning model better than those taught using the Make A Match learning model in class V SD Negeri 094166 Sidotani I Academic Year 2022/2023.